Insegurança alimentar, habitos alimentares e doenças crônicas no Brasil - Stegues, Gustavo da Silveira (2025)
Food insecurity worsens the population's health, especially among the most vulnerable, highlighting the need for integrated public policies. This dissertation investigates the interaction between food insecurity, dietary habits, and non-communicable diseases (NCDs) in Brazil, based on two scientific articles that explore different dimensions of the subject. The research recognizes that food insecurity reflects historical socioeconomic inequalities and has direct implications for public health, particularly in the rise of NCDs. The first article, supported by bibliographic references, applied the Alkire-Foster methodology to measure food and health deprivations across Brazil’s macro-regions using data from Vigitel 2021. The results showed that 25.59% of the population faces deprivations, with an average intensity of 47.01%. The North and South regions exhibited the highest indices, underscoring critical regional disparities in food security. The second article developed a fuzzy health index to evaluate the relationship between living conditions, diet, and NCDs. The findings confirmed that food insecurity and inadequate dietary habits perpetuate cycles of vulnerability and harm health, emphasizing the importance of multifactorial indicators for monitoring public health conditions. Both studies demonstrated that food insecurity in Brazil is multidimensional, reflecting structural inequalities and impacting the prevalence of NCDs, especially among vulnerable populations. It concludes that addressing food insecurity and its impacts requires integrated policies that consider regional specificities, strengthen family farming, and promote food education. This work enhances the understanding of food, health, and inequalities, contributing to policies that prioritize equity and social well-being.